2017
DOI: 10.3389/fpsyg.2017.00779
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Gambling Problems on Online Electronic Gaming Machines, Race Betting and Sports Betting

Abstract: Growth of Internet gambling has fuelled concerns about its contribution to gambling problems. However, most online gamblers also gamble on land-based forms, which may be the source of problems for some. Studies therefore need to identify the problematic mode of gambling (online or offline) to identify those with an online gambling problem. Identifying most problematic form of online gambling (e.g., EGMs, race betting, sports betting) would also enable a more accurate examination of gambling problems attributab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
2
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 53 publications
4
65
2
5
Order By: Relevance
“…These results differ from those reported for an Australian sample of sports bettors in which problem gambling rates for males were significantly higher than for women and follow-up studies where being male was a predictor of problem sports betting (Hing et al 2017a). The findings in the present study also contradict the traditional gender imbalance found in most online gambling studies (Wood and Williams 2009) but not in the context of sports betting in particular, in which previous research with online gamblers playing on the bwin website reported non-significant differences between women and men .…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…These results differ from those reported for an Australian sample of sports bettors in which problem gambling rates for males were significantly higher than for women and follow-up studies where being male was a predictor of problem sports betting (Hing et al 2017a). The findings in the present study also contradict the traditional gender imbalance found in most online gambling studies (Wood and Williams 2009) but not in the context of sports betting in particular, in which previous research with online gamblers playing on the bwin website reported non-significant differences between women and men .…”
Section: Discussioncontrasting
confidence: 56%
“…Cross-sectional studies of Australian sports bettors have identified risk factors for gambling problems such as being male, young, never married, living alone or in a group household, and with higher level education . Also, Australian sports bettors with a language other than English as their mother tongue are more likely to engage in problem betting (Hing et al 2017a). Australian sports bettors prefer simpler bets in which the odds are easier to estimate, particularly when placing bets for a winner.…”
Section: A Brief Overview Of Sports Bettingmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in sharp contrast with recommendations for responsible gambling, which is principally making informed betting choices and keeping betting within predetermined, affordable time and spending limits (Hing et al 2016a). Recent research from Australia has indicated that between one third and one half of all bets placed online were considered by participants to be impulse bets rather than carefully evaluated betting selections (Hing et al 2015(Hing et al , 2018a, and it is widely acknowledged that impulsive betting is predictive of gambling problems (Hing et al 2015(Hing et al , 2016b.…”
Section: Introductionmentioning
confidence: 99%
“…In their opinion, the battle for quantity is over and now each operator will have to focus on offering a distinctive product that meets the demands of quality of its audience. Personalisation of the betting experience appears to be crucial in a market where product differentiation is non-existent and price elasticity very limited (Hing, 2014).…”
Section: Mobile Technologiesmentioning
confidence: 99%